Genomic analysis of a Palestinian family with inherited cancer syndrome: a next-generation sequencing study - Fares, Eman; Thawabtah, Rua; Sallam, Husam; Khatib, Areej A. H.; Qutob, Nouar; Salah, Zaidoun (Frontiers in Genetics, 2023)
Familial predisposition is a strong risk factor for different types of cancer and accounts for around 10% of the cases. In this study, we investigated cancer predisposition in a Palestinian family using Whole Exome Sequencing (WES) technologies. In this study we focused more on cutaneous melanoma (CM). Our analysis identified three heterozygous rare missense variants, WRN ( p.L383F and p.A995T) and TYRP1 (p.T262M) and a pathogenic homozygous missense mutation in ERCC2 (p.R683Q) . Although WRN and TYRP1 genes and their variations were correlated with different types of cancer including melanoma, the currently identified WRN and TYRP1 variants were not reported in melanoma cases before. The pathogenic mutation was segregated with the clinical phenotypes and found in the two affected brothers one with CM and the other with brain tumor and was confirmed by sanger sequencing analysis. Segregation analysis of this mutation revealed that family members are either heterozygous or wild-type. Our findings confirm that the homozygous ERCC2 (p.R683Q) mutation is the causative mutation for melanoma and other cancer types in the family. Our work highlights the value to decipher the mutational background of familial cancers, especially CM, in the Palestinian population to guide diagnosis, prevention, and treatment of affected patients and their families.